Congenital syphilis prevention in the context of methamphetamine use and homelessness. Issue 3 (27th March 2022) - Plotzker, Rosalyn E.; Burghardt, Nicole O.; Murphy, Ryan D.; McLean, Rachel; Jacobson, Kathleen; Tang, Eric C.; Seidman, Dominika
Abstract: Background and Objectives: Congenital syphilis (CS) is increasing in the United States and is associated with intersecting social and structural determinants of health. This study aimed to delineate birthing parent characteristics associated with CS in an adjusted model. Methods ( n = 720): People diagnosed with syphilis during pregnancy from 2017 to 2018 who were interviewed and linked to infants in the California state surveillance system were included (herein, "birthing parents"). Sociodemographic and clinical CS risk factors informed a stepwise multivariable logistic regression model in which the outcome of interest was infants born with CS. CS prevention continuums delineated the proportion of pregnant people with syphilis who completed steps (e.g., prenatal care entry, syphilis testing, treatment) needed to prevent CS; the outcome was delivering an infant without CS. We stratified continuums by homelessness and methamphetamine use to explore differences in CS outcomes. Results: Of 720 birthing parents, 245 (34%) delivered an infant with CS. Although CS was initially associated with homelessness (odds ratio [OR] = 2.5, 95% confidence interval [CI]: 1.6, 4.0) and methamphetamine use (OR = 2.1, 95% CI: 1.4, 3.1), the addition of prenatal care into a final adjusted model attenuated these associations to not significant. In CS prevention continuums, delivering an infant without CS was less likely for people who reported methamphetamine use ( p < .001) and/or homelessness ( p < .001). However, when examining only those who received prenatal care, statistical differences for these predictors no longer existed. In the final adjusted model the following were associated with CS: no prenatal care (OR = 16.7, 95% CI: 9.2, 30.3) or late prenatal care (OR = 2.9, 95% CI: 1.9, 4.2); early stage of syphilis (OR = 2.6, 95% CI: 1.8, 3.7); living in Central California (OR = 2.1, 95% CI: 1.1, 4.2). Conclusions and Scientific Significance: This is the first analysis to explore birthing parent characteristics associated with delivering an infant with CS in an adjusted model. We demonstrate that prenatal care, when accessed, can result in effective CS prevention among people who are unhoused and/or using methamphetamine equally well compared to counterparts without these risk factors.